2016
DOI: 10.1038/srep28888
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting VEGF-A paracrine and autocrine loops by targeting SHP-1 suppresses triple negative breast cancer metastasis

Abstract: Patients with triple-negative breast cancer (TNBC) had an increased likelihood of distant recurrence and death, as compared with those with non-TNBC subtype. Regorafenib is a multi-receptor tyrosine kinase (RTK) inhibitor targeting oncogenesis and has been approved for metastatic colorectal cancer and advanced gastrointestinal stromal tumor. Recent studies suggest regorafenib acts as a SHP-1 phosphatase agonist. Here, we investigated the potential of regorafenib to suppress metastasis of TNBC cells through tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Regorafenib, a multikinase inhibitor, is used to treat different kinds of cancer. Su et al [ 19 ] found regorafenib reduced protein expression of VEGF through suppression of signal transducer and activator of transcription 3 (STAT-3) activation in triple negative breast cancer cells in vitro and in vivo . Chen et al [ 20 ] found regorafenib triggered p53-upregulated modulator of apoptosis (PUMA)-mediated apoptosis through induction of NF-κB pathway in colorectal cancer in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Regorafenib, a multikinase inhibitor, is used to treat different kinds of cancer. Su et al [ 19 ] found regorafenib reduced protein expression of VEGF through suppression of signal transducer and activator of transcription 3 (STAT-3) activation in triple negative breast cancer cells in vitro and in vivo . Chen et al [ 20 ] found regorafenib triggered p53-upregulated modulator of apoptosis (PUMA)-mediated apoptosis through induction of NF-κB pathway in colorectal cancer in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms underlying WMJ‐8‐B′s activation of SHP‐1 or Sp1 signalling in MDA‐MB‐231 cells remains to be elucidated. Su et al () recently showed that SHP‐1 expression is inversely correlated with STAT3 phosphorylation in human TNBC cell lines and clinical breast cancer specimens. We noted, in the siRNA experiments, that WMJ‐8‐B slightly increased SHP‐1 levels in MDA‐MB‐231 cells in the absence of SHP‐1 siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Nintedanib has been found to elevate SHP‐1 activity through interacting with SHP‐1 at Glu524 through hydrogen bonding in a docking model (Tai et al ., ). Although many SHP‐1 activators have been identified (Chen et al ., ,b,c; Liu et al ., ; Su et al ., ,b, ; Tai et al ., ), the structure and activity relationship still needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%